ANALISIS MISKONSEPSI PESERTA DIDIK PADA MATERI PERSAMAAN LINIER SATU VARIABEL DALAM BUKU MATEMATIKA TINGKAT SMP - Adam Rafli; Intan Ria Utami Limbong; Venesya Pitta Rezeki Siburian; Samuel Tappin Martua Sitorus; Edwina Pardosi; Wingston Leonard Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze various forms of misconceptions in the understanding of students regarding the material of Linear Equations in One Variable (LEOV) found in junior high school mathematics textbooks. The method used in this study is qualitative descriptive analysis by examining the material, examples, and questions that have the potential to cause misconceptions. Data were obtained through content analysis of the books and identifying conceptual errors that may be experienced by students. The results of the study indicate that there are still several misconceptions that arise regarding the material, including errors in understanding the concept of an equation as an open statement, mistakes in writing Linear Equations in One Variable, and errors in operating that material. These findings demonstrate the need for improvement in all forms of material presentation and teaching strategies to minimize misconceptions. Thus, this analysis is expected to provide input for teachers and textbook authors to enhance the quality of mathematics education at the junior high school level.